Pendekatan Partisipatif Dalam Penganggaran Berbasis Kinerja: Studi Program ALAKE Singkawang: Participatory Approach in Performance-Based Budgeting: A Study of the ALAKE Program in Singkawang - Firdaus, Firdaus; Rinaldi, Hasymi (Polytechnic of State Finance STAN, 2025)
Fiscal decentralization in Indonesia has not yet achieved its expected outcomes in promoting efficiency, transparency, and environmental sustainability. To address these issues, the Indonesian government introduced the Ecological Fiscal Transfer (EFT) framework, which integrates ecological indicators into fiscal allocation formulas. One of its local adaptations is the Alokasi Anggaran Kelurahan Berbasis Ekologi (ALAKE), or Ecological Village Budget Allocation, implemented in Singkawang City. This study aims to analyze the implementation of ALAKE within the EFT policy framework and identify strategic programs and sub-activities that support its performance indicators. A mixed-methods approach was applied through document analysis, field observations, and Focus Group Discussions (FGD) involving 26 urban villages. The findings reveal that ALAKE effectively integrates fiscal and ecological goals through participatory planning and green budget tagging. Priority actions include waste management, drainage maintenance, urban greening, and disaster preparedness. However, challenges remain in data standardization, administrative capacity, and incentive mechanisms. The study concludes that ALAKE represents an innovative micro-level fiscal policy instrument that links ecological performance with budgetary incentives, offering a replicable model for sustainable local governance and equitable fiscal policy in other regions of Indonesia.